VA Research and Operations Uniting to Combat COVID-19 Inequities (Mary Ann Liebert, 2023)
As novel coronavirus 2019 disease (COVID-19) began to spread across the United States in early 2020, health care systems faced extreme demands on resources. As the country's largest single-payer health care system, the U.S. Department of Veterans Affairs (VA) was uniquely positioned to study how the virus impacted different communities and work to improve care provided to all. Early on, a literature review of prior epidemics revealed that occupational exposures and an inability to socially distance could impact some groups more than others. The VA's Office of Health Equity leveraged a general sense of community to create a collaborative research space and a dedicated analytic space to inform pandemic operations. VA researchers and operations staff were able to quickly share information and respond to updates to produce accurate and reliable publications for medical professionals and the general public. Partnerships with VA Medical Centers and Veteran Service Organizations helped to increase communication across the nation and determine the most critical needs. Although COVID-19 was dynamic in nature, VA's intentional examination of social and structural factors was crucial in informing a more equitable approach. Moving forward, these inequities must be intentionally addressed in future pandemic responses.